A cyclization-induced emission enhancement (CIEE)-based ratiometric fluorogenic and chromogenic probe for the facile detection of a nerve agent simulant DCP1. Issue 47 (14th June 2015) - Mahapatra, Ajit Kumar; Maiti, Kalipada; Manna, Saikat Kumar; Maji, Rajkishor; Mondal, Sanchita; Das Mukhopadhyay, Chitrangada; Sahoo, Prithidipa; Mandal, Debasish
<x xml:space="preserve">Abstract</x> The first ratiometric fluorescent probe for the detection of a nerve agent simulant was developed based on tandem phosphorylation and intramolecular cyclization.